Effects of threshold pressure loading exercises applied to inspiratory muscles in taekwondo athletes on the concentration and utilization of lactate - Koç, M.; Saritas, N.; Coskun, B.; Akkurt, S. (Journal of Human Kinetics, 2025)
This study examined the effects of different inspiratory muscle training (IMT) on lactate concentration and utilization during high-intensity exercises. Participants were divided into the following three groups: a chronic inspiratory training group (CRG), an acute inspiratory training group (ARG), and a control group (CG). Participants in the CRG accomplished IMT at an exercise intensity of 60-90% of the maximum inspiratory pressure (MIP) with 30 breaths twice a day for 8 weeks, and those in the ARG performed IMT at an intensity of 40-50% of the MIP for approximately 20 min in the pre-training warm-up phase three times a week. Body composition tests, maximum oxygen uptake, anaerobic power tests, and lactate concentrations of participants were evaluated before and after the intervention. Three consecutive anaerobic power tests (Wingate) were performed to observe changes in lactate concentration and utilization during high-intensity exercises. Blood lactate concentrations were measured immediately at the end of each anaerobic power test, after a 75-s rest, and during passive rest at the 2nd, 3rd, 4th, 5th, 10th, and 15th min of recovery. The results of the analysis of variance (ANOVA) revealed a significant decrease in blood lactate concentration only in the CRG immediately after the first Wingate test, whereas significant differences in the ARG and the CG were observed after the third Wingate test. After the last Wingate test, a significant decrease was observed after 5 min of recovery in the CRG and after 10 and 15 min of passive rest in both training groups. Herein, we conclude that IMT decreases blood lactate concentration after intense exercise and accelerates lactate utilization during recovery.